Implementasi Revolusi Industri 4.0 Pada Industri TPT (Tekstil dan Produk Tekstil) di Kecamatan Pringapus - Ramadhanti, Dita; Hardati, Puji (Geo-Image, 2021)
Pringapus district is a district with a variety of TPT (Textile and Products Textile) industries, the total are 54consisting of 11 home industries, 25 small industries, 7 medium industries, and 11 large industries. The purposeof this study is to know the implementation of the 4.0 industrial revolution in the textile industry and textileproducts in Pringapus district in the factors of raw materials, production activities, marketing, the salary system,and health assistance applied by the textile and product textile industries. The sampling technique uses to knowthe implementation of the 4.0 industrial revolution in the textile and product textile (TPT) industry andemployment is purposive sampling because the researchers took 3 industries consists of 1 home industry, 1 smallindustry, and 1 medium industry in the Pringapus district. The data analysis technique uses qualitativedescriptions by describing the answers of the respondents. The results showed that the textile industry and textileproducts in Pringapus District that implement the whole of industry 4.0 are medium and largescale industries.While in small industries the implementation it only lies in the process of obtaining raw materials, productionmachines, and online marketing. In the home industry, the application of industry 4.0 only on product marketingtechniques using the online system. Kecamatan Pringapus merupakan Kecamatan dengan industri TPT (Tekstil dan Produk Tekstil)yang bervariasi yaitu sebanyak 54 yang terdiri dari 11 industri rumah tangga, 25 industri kecil, 7industri sedang/menengah dan 11 industri besar. Tujuan penelitian ini adalah untuk mengetahuiimplementasi revolusi industri 4.0 pada industri tekstil dan produk tekstil di Kecamatan Pringapusmelalui faktor bahan baku, kegiatan produksi, pemasaran, sistem upah dan bantuan kesehatan yangditerapkan oleh industri tekstil dan produk tekstil. Teknik sampel yang digunakan untuk mengetahuiimplementasi revolusi industri 4.0 pada industri tekstil dan produk tekstil (TPT) dan penyerapantenaga kerja adalah purposive sampling karena peneliti mengambil 3 industri yang masing-masingterdiri dari 1 industri rumah tangga, 1 industri kecil dan 1 industri sedang di Kecamatan Pringapus. Teknik analisis data menggunakan deskripsi kualitatif dengan mendeskripsikan jawaban dariresponden. Hasil penelitian menunjukkan bahwa industri tekstil dan produk tekstil di KecamatanPringapus yang secara keseluruhan menerapkan industri 4.0 adalah industri skala sedang dan besar,sedangkan industri kecil penerapan hanya terletak pada proses pemerolehan bahan baku, mesinproduksi dan pemasaran yang dilakukan secara online. Industri skala rumah tangga penerapanindustri 4.0 hanya pada pada teknik pemasaran produk yang dilakukan secara online.